NH2-Functionalized Graphene Quantum Dots for Hg2+ Detection: A DFT/TD-DFT Study of Fluorescence Quenching Mechanism - Berlian Sitorus; Dian Pratiwi; Ihsanul Arief (Jurnal Kimia Riset, 2026)
Graphene Quantum Dots (GQDs) are promising nanocarbon materials for fluorescence sensing applications; however, pristine GQDs generally exhibit limited selectivity toward specific metal ions, thus requiring functional modification. This study employs Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TD-DFT) computational approaches to investigate the effect of amine (–NH2) functionalization on the electronic and optical properties of GQDs and their potential application for mercury ion (Hg2+) detection. The –NH2 groups were introduced at four different edge carbon positions to evaluate the influence of substitution sites on structural stability, electronic properties, and optical response of GQDs. The results indicate that –NH₂ functionalization increases the HOMO energy level and reduces the band gap, with variations determined by the substitution position, resulting in shifts in the absorption and fluorescence spectra. Interaction with Hg2+ ions induce notable changes in the frontier molecular orbitals and may promote fluorescence quenching through a non-radiative charge transfer mechanism. Overall, these findings suggest that NH₂-functionalized GQDs possess promising characteristics for potential turn-off fluorescent sensing applications and provide theoretical insights for the rational design of nanocarbon-based sensors.